Effect of glass fiber on the permanent deformation of numerically modelled wearing courses in ANSYS (LACCEI, 2024)
The continuous increase in the number of heavy vehicles usually causes that the wearing course present greater permanent deformation in less time, due to its low resistance to traffic loads. Given this, different laboratory studies have tried to reduce permanent deformation through the application of additives, such as glass fiber. That is why the present investigation analyses the effect of glass fiber on the permanent deformation of a numerically modelled wearing course in ANSYS. First, the mechanical properties of asphalt mixtures with different percentages of glass fiber were collected, in order to represent their values as a material in the numerical model. Then, the simulation of the Marshall stability and flow test was carried out to configure the materials created in the software. Finally, the numerical model of the wearing course was solved, and its permanent deformation was obtained. The results indicated that glass fiber reduces the permanent deformation of the wearing course by an average of 15%, unlike mixtures without fibers. In addition, it was established that the ideal percentage range that can be applied to the mixture to improve its performance is 0.25% - 0.40% glass fiber.